Stretching the boundaries: Malaysian ESL learners' evaluative reactions to inner circle English accents - Pilus, Zahariah; Zakaria, Nur Shahida; Zakaria, Muhamad Khairul; Wahid, Ridwan (John Benjamins Publishing Company, 2019)
Nowadays, international communication using English as the medium is a common occurrence. To communicate effectively, English as a second language (ESL) speakers need to possess relevant communicative skills including understanding and being familiar with inner circle accents. This paper seeks to find out ESL learners' evaluative reactions to four inner circle accents, representing British, American, Australian and New Zealand English varieties, through an accent perception and a survey task conducted on Malaysian undergraduates at a public university in Malaysia. The participants responded to descriptors on speaker attributes categorized into three dimensions: competence, social appeal and accent preference while or after listening to a recorded passage read in one of the four accents by male and female speakers. The learners showed a tendency to prefer certain accents more than others. In general, the best rated accent was the British accent for the male speakers and the American accent for the female speakers. The New Zealand accent was rated the lowest among the male speakers and one of the lowest among the female speakers. The study also found that speaker's competence, speaker's social appeal and accent preference were positively correlated. These findings highlight the importance of listening practices and exposure to various English accents in ESL classrooms to prepare students for international and intercultural communication. © John Benjamins Publishing Company